Community-based breeding programs can realize sustainable genetic gain and economic benefits in tropical dairy cattle systems - Hunde, Direba; Tadesse, Yosef; Tadesse, Million; Abegaz, Solomon; Getachew, Tesfaye (Frontiers in Genetics, 2024)
Implementing appropriate breeding program is crucial to control fluctuation in performance, enhance adaptation and further improve the crossbred population. Five alternative breeding programs (BPs) were modeled considering available breeding unit in the study area, and the existing scenario of crossbreeding practices and future prospect of dairy research and development in Ethiopia. The study targeted 143,576 crossbred cows of about 54,822 smallholder households in the Arsi, West Shewa and North Shewa zones of Oromia Region as well as North Shewa zone of Amhara Region. The alternative BPs include conventional onstation progeny testing (SPT), conventional on-farm progeny testing (FPT), conventional onstation and on-farm progeny testing (SFPT), genomic selection (GS) and genomic progeny testing (GPT). Input parameters for modeling the BPs were taken from the analysis of long-term data obtained from the Holetta Agricultural Research Center and the survey conducted in the study area. ZPLAN+ software was used to predict estimates of genetic gain (GG) and discounted profit for goal traits. The predicted genetic gain (GG) for milk yield (MY) per year were 34.52 kg, 49.63 kg, 29.35 kg, 76.16 kg and 77.51 kg for SPT, FPT, SFPT, GS and GPT, respectively.The GG of the other goal traits range from 0.69 to 1.19 days per year for age at first calving, from 1.20 to 2.35 days per year for calving interval and from 0.06 to 0.12 days per year for herd life. Compared to conventional BPs, genomic systems (GPT and GS) enhanced GG of MY by 53% to 164%, reduce generation interval up to 21% and improved accuracy of test bull selection from 0.33 to 0.43. The discounted profit of the BPs varied from 249.58 Ethiopian Birr (ETB, 1 USD = 39.55696 ETB) per year in SPT to 689.79 ETB per year in GS. Genomic selection outperforms the SPT, SFPT and FPT by 266, 227% and 138% of discounted profit, respectively.Community-based crossbreeding accompanied by genomic selection (GS) and gradually support it with progeny testing (GPT) are recommended in this order as the main way forward to attain better genetic progress in dairy farms in Ethiopia and in similar scenario elsewhere in tropical countries.